(3edJbWGJ ef cJGH fXe GdOQQ hGdYbjGf aj HjGf TQa Hfj RjGfs - (3eMeO Hf YHO Gddg Hf YHO GdLdjd GdJfSjs; (3GdJfSj , eMeO Hf YHO Gddg Hf YHO GdLdjd, CHh YHO Gddg,J (B899 (3g` s
(3ChdgG (B:s
(3GdMeO ddg aGdb GdEUHGM hLGYd Gddjd ScfkG heNJQY GdCQhGM s
(3BNQgG (B:s
(3eHJhQ, JfJgi Hbhdg(B: (3EPG cfJ JLYd YbHi GdCehQ heGdc Mhd hdG ebOQg ade PG GdYfG hYdi e GdCSi heqeG GdMPGoQ haje GdTQg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B34 - (3U(B103s
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B238 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B222s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B415 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs